The Effectiveness of the Algodoo-Assisted IBMRO Model in Improving Physics Problem-Solving Skills - Joko Siswanto; Nur Khoiri; Hanandita Veda Saphira (Jurnal Pendidikan IPA Indonesia, 2025)
The IBMRO (Investigation-Based Multiple Representation Online) learning model is designed to improve physics problem-solving skills. However, its implementation requires the right tools so that the objectives can be achieved even though the learning process is carried out online. This study used Algodoo as a learning tool in the IBMRO model on parabolic motion. This study aims to analyze the effectiveness of the Algodoo-assisted IBMRO model in improving students' physics problem-solving skills. This research employed a pre-experimental one-group pre-test and post-test design, with 96 students divided into three classes. Before and after the learning process, students were given tests (pre-test and post-test). During the learning process, observations were made of student activities. After the learning was completed, students were given a questionnaire to assess their understanding of the learning. The pre-test and post-test scores were analyzed using paired t-test, Wilcoxon test, and n-gain. The percentage of observation and questionnaire data was calculated. The results showed that the average score of students' physics problem-solving skills increased significantly a = 5%, The average n-gain of physics problem-solving skills was in the medium category, the average n-gain of each indicator of physics problem-solving skills was in the medium to high category, student activities were relevant to learning, and students had a good response to learning. This study concludes that the Algodoo-assisted IBMRO model is effective in improving students' physics problem-solving skills.